ASSET RENTAL INFORMATION SYSTEM AND WEB-BASED FACILITIES AT ANDALAS UNIVERSITY - Zainul Efendy; Ilham Eka Putra; Rangga Saputra (JUTEI (Jurnal Terapan Teknologi Informasi), 2019)
Andalas University is the oldest university outside Java Island, and is the fourth oldest university in Indonesia. The University of Andalas also has assets and facilities such as buildings, land, equipment, campus buses and official vehicles managed by the administration acnd general 2 fields under the leadership of the Vice Rector 2, the assets and facilities available at the university andalas are also leased to people who want to rent or use existing facilities. Payment transactions and report recaps are still done manually this makes managers in recording transaction data becomes difficult. The status of pay by the lessee is difficult to track if the leader requests the report results. Therefore we need an information system to manage rental transaction and facilities at university andalas, that is information system that can recap asset, tenant and payment data. The research method used is System Development Life Cycle (SDLC) research, in SDLC development process consisting of system planning, system analysis, system design, and system implementation. With this information system is expected both parties' transactions can be easily and mutually beneficial and the storage can also supervise transactions that exist wherever they are